THERMOLYSIS AND KINETICS OF SCRAP TYRE AND BAGASSE FOR ENERGY UTILIZATION - Ndalila, Petro; Mhilu, Cuthbert F; John, Geoffrey R (Tanzania Journal of Engineering and Technology, 2017)
The increase of energy demand has brought concern to find alternative fuel that will at least sustain the requirement. Bagasse and scrap tyre are waste generated in our industrial activities, which can be used in energy production to subsidize the demand. This paper, aim to study the decomposition behaviour and kinetics of biomass (bagasse) and scrap tyre as preliminary stage of fuel sample analysis to be considered for energy production in gasification/combustion or pyrolysis facilities. The behaviour demonstrated with thermogravimetric analyzer (TGA), shows that all samples have high volatile amount release, 84.21% for bagasse and 85.08% for scrap tyre, which means all are suitable for pyrolysis. However, scrap tyre is most suitable for gasification or combustion due to its high energy content, high ash content and low moisture than bagasse. The determined kinetic parameter were activation energy (E) and pre-exponential factor (A) for hemicellulose/oil as first release composite and cellulose/elastomer as second composite of the analyzed bagasse/scrap tyre samples. The hemicelluloses of bagasse exhibited highest value of activation energy and pre-exponential factor (E=178.191 kJ/mol, and A=1.74Ã—10 16 ) than oil of scrap tyre (E=41.113 kJ/mol, and A= 495.5), which means bagasse is suitable candidate for gasification process due to high operating temperature. With this respect of the study, all candidates may be suitable for pyrolysis or gasification/combustion process. However, for environmental consideration scrap tyre is not suitable due to high sulphur (S) and nitrogen (N) content resulting to high emission of SO X and NO X .